2015
DOI: 10.7314/apjcp.2015.16.10.4377
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor 2 and 5 Expressions in Gastroenteropancreatic Neuroendocrine Tumors in Turkey

Abstract: Background: Gastroenteropancreatic neuroendocrine tumors (GNs) are slow growing and although their incidence has increased in recent years, they are relatively rarely seen. Somatostatin analogues are used in the treatment of GNs that express somatostatin receptor (SR). We aimed to investigate the expression of SR2 and SR5 in GNs. Materials and Methods: In this study the expression of SR2 and SR5 was investigated immunohistochemically in 49 cases (26 males, 23 females) diagnosed and graded with GN according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…SSTR2 expression was identified in approximately 70% of rectal NETs in the present study. Previous studies demonstrated that SSTR2 expression in a small cohort of rectal NETs (range 3–13 patients) and the majority of them were included as a component of left colon or colorectal NET cohorts 18 , 38 41 . The proportion of SSTR2 expression in rectal NETs ranged from 14 to 100% in the previous studies 18 , 38 , 39 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…SSTR2 expression was identified in approximately 70% of rectal NETs in the present study. Previous studies demonstrated that SSTR2 expression in a small cohort of rectal NETs (range 3–13 patients) and the majority of them were included as a component of left colon or colorectal NET cohorts 18 , 38 41 . The proportion of SSTR2 expression in rectal NETs ranged from 14 to 100% in the previous studies 18 , 38 , 39 , 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Octreotide and lanreotide, well-known SSA, have high affinity for SSTR-2 and -5. However, it has been reported that SSTR-5 was expressed in 0% of neuroendocrine carcinomas, while it was positive in 81.8 and 60% of G1 and G2 neuroendocrine tumors, respectively [69,70] . Conversely, only a single study showed a 100% SSTR-2 expression rate in gastroenteropancreatic neuroendocrine carcinoma [69] , but this study included only one rectal neuroendocrine carcinoma case, which is inadequate evidence to support the introduction of SSA for neuroendocrine carcinoma components.…”
Section: Management Of Recurrent or Unresectable Tumorsmentioning
confidence: 97%
“…IHC and autoradiography confirmed that SSTRs 1, 2 and 5 were the most frequent receptors in GEP NETs, whereas the expression of SSTR3 was quite variable (Kimura et al 1999, Kulaksiz et al 2002, Papotti et al 2002, Bertherat et al 2003, Reubi & Waser 2003, Yerci et al 2015, Kasajima et al 2017.…”
Section: Expression Of Sstr Subtypes In Netsmentioning
confidence: 99%